Pakistan Army Green Book 2006 : Terrorism - Pakistan Army; Editorial Board : Brig. Muhammad Mushtaq Bhatti; Lt. Col. Taimur Sabir Bhatti and Lt. Col. Naseer Ahmad Satti (GHQ, Rawalpindi Pakistan Army, 2006)
Content of the book are the writers' personal views and are not be taken as official opinion/policy
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals